Pemberdayaan Kader dan Keluarga dalam Penerapan Piramida Gizi Seimbang dan Pemantauan Tumbuh Kembang Balita Sebagai Upaya Pencegahan Stunting di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2023 - Siti Nurmawan Sinaga; Febriana Sari; Sonia Novita Sari (FKIP, Universitas Palangka Raya, 2023)
Stunting is a chronic nutritional problem that is a national development priority listed in the 2020-2024 RPJMN. Trends and targets for reducing stunting have progressed but are not yet significant. Of course, several causal factors are still found, so empowerment is needed to accelerate stunting reduction. The main focus in handling stunting is the First 1000 Days of Life (HPK) which is carried out at Posyandu. Cadres who play an important role in driving posyandu are expected to have good knowledge and high motivation in efforts to prevent stunting. The aim of this activity is to empower health cadres and families to increase knowledge about preventing stunting by implementing the Balanced Nutrition Pyramid and Monitoring the Growth and Development of Toddlers. The target of this activity was cadres and families in Bangun Rejo Village, Tanjung Morawa District with a total of 42 participants (21cadres and 21 families). Empowerment activities use the lecture method followed by a question and answer session. The results of the activity showed that 71.4% of cadres and families had good knowledge. It is hoped that empowerment of cadres and families can be implemented consistently and continuously so that it can improve cadre performance and family understanding in implementing the Balanced Nutrition Pyramid and Monitoring Toddler Growth and Development as an Effort to Prevent Stunting